Optimisation of Bioethanol Yield from Oil Palm Trunk Sap - Rossyuhaida, Mohd Zakria; Chua, Gek Kee; Jolius, Gimbun; Nor Shahirah, Mohd Nasir; Sook, Fun Pang; Mohd Fazli, Farida Asras; Cheng, C. K.; Ahmad Ziad, Sulaiman (Universiti Teknikal Malaysia Melaka (UTeM), 2015)
This paper presents the effect of nutrients addition and fermentation microorganism on bioethanol yield from oil palm trunk sap. Six microorganisms namely, Saccharomyces cerevisiae ATCC 9763, Saccharomyces cerevisiae ATCC 26602, baker’s yeast, Kluyveromyces marxianus ATCC 46537, Zymomonas mobilis ATCC 29501 and Escherichia coli ATCC 10536 were screened for ethanol production at fixed temperature, pH, agitation and inoculum size. The sugar and ethanol content were determined using a high performance liquid chromatography (HPLC). The results showed that K. marxianus produced the highest ethanol yield (60.9%) at a shorter fermentation time (16h) compared to the other strains. Six nutrients, namely, ammonium sulphate, di-ammonium hydrogen phosphate, magnesium sulphate, β-alanine, calcium chloride and potassium dihydrogen phosphate were screened using this strain and the highest ethanol yield (98.62%) was achieved in fermentation supplemented by magnesium sulphate and β-alanine. Subsequently, the optimisation study using a reseponse surfae methodology found the optimum value of magnesium sulphate was 7.93 g/L and 0.90 g/L for β-alanine. Under the optimum conditions, the predicted ethanol concentration was 34.58 g/L while the experimental value (35.50 g/L) was in agreement with the predicted value with 2.66% error.